Manajemen Accounting dan Pengembangan Produk Low Density Polypropylene (LDPE) Bank Sampah Bolo Larahan - Fatchur Rohman; Yanto Yanto; Nor Diah Handayani; Sri Iftiana Seftiani; Muhammad Riza Aftoni (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Balikpapan (LPPM UNIBA), 2022)
Garbage is one of the complex problems faced by both developing and developed countries in the world. Waste processing continues to be developed in Indonesia to reduce the risk of environmental pollution, one of which is the existence of a waste bank to attract and increase public awareness. One of the waste banks in Pati Regency is the Bolo Larah Waste Bank. Based on the results of surveys and observations, there are several problems faced by the waste bank, including the limited administration of waste savings management from the community as customers, limited information and ways to process LDPE type plastic waste into products of economic value, and limited knowledge from partners about determining development costs. junk products. The method used in this service activity begins with preparation, development of the SIMASH waste bank application that provides information for management / manager decision making, waste bank management training and calculating the price of waste products that have been developed. The result of this service activity is that partners get information and training on the use of the SIMASH application which can provide accounting information for decision making, training on the development of LDPE type waste products into paving blocks and training has been carried out in calculating the cost of products developed by the bolo larahan waste bank.